2014
DOI: 10.1073/pnas.1318967111
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional cell migration does not follow a random walk

Abstract: Cell migration through 3D extracellular matrices is critical to the normal development of tissues and organs and in disease processes, yet adequate analytical tools to characterize 3D migration are lacking. Here, we quantified the migration patterns of individual fibrosarcoma cells on 2D substrates and in 3D collagen matrices and found that 3D migration does not follow a random walk. Both 2D and 3D migration features a non-Gaussian, exponential mean cell velocity distribution, which we show is primarily a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
388
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(439 citation statements)
references
References 29 publications
25
388
3
5
Order By: Relevance
“…The images were analyzed using Imaris spot analysis software (Imaris 8.1; Bitplane) to track the time-dependent mobility. The 3D migration analysis was performed following the strategy developed by Wirtz and coworkers (29,30). A minimum of 100 individual cells at each point were tracked to generate x, y, and z coordinates at each time point.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The images were analyzed using Imaris spot analysis software (Imaris 8.1; Bitplane) to track the time-dependent mobility. The 3D migration analysis was performed following the strategy developed by Wirtz and coworkers (29,30). A minimum of 100 individual cells at each point were tracked to generate x, y, and z coordinates at each time point.…”
Section: Methodsmentioning
confidence: 99%
“…By choosing the time frame with the most visible cells we could maximize the sample size of cells that could be analyzed. Finally, velocity and speed profiles, MSDs, and trajectory plots were calculated using code adapted from Wirtz and coworkers (29,30) for triplicate tracking trials (n = 3). The statistical analysis was performed using MATLAB (Mathworks, Inc.) to calculate the mean, SD, and SE of the mean.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors use the inertia term m i dv i /dt to mimic the effect of persistence [28] while in principle it can be directly simulated using a memory term. In this case, Γ cx i j v k (x ∈ {c, s}, k ∈ {i, j}) has to be replaced by…”
Section: Basic Conceptsmentioning
confidence: 99%
“…During metastasis in cancer, cells detach from the tumor and migrate through the stroma. Studies have revealed that cells remodel the matrix around them [26,27], thereby possibly creating trails for other cells [28,29].…”
Section: Introductionmentioning
confidence: 99%